Peculiarities of Compensation Calculation for Illegal Use of Trademarks - Permyakova N. А. (Vestnik Omskoj Ûridičeskoj Akademii, 2013)
The article deals with the issues of compensatory method application of violated rights protection. Here are revealed the problematic issues of law enforcement practice in bringing to civil liability; Art. 1515 Civil code of the Russian Federation.